Abstract Number ‐ 175: First Pass Results of Mechanical Thrombectomy with two‐drop zone NeVaTM Device - Serdar Geyik; Arsida Bajrami; Ozgur Ertugrul; Songul Senadim; Eren Erdem; Feyyaz Baltacioglu; Raul G Nogueira (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Occlusive thrombi in acute ischemic stroke can be in various types which limits the success of the thrombectomy.The NeVaTM(Vesalio, Nashville, Tennessee) thrombectomy device was originally designed for all types of clot. Our aim was to evaluate the efficacy and safety of the NeVaTMdevice for mechanical thrombectomy. Methods Retrospective review of prospectively collected mechanical thrombectomy database revealed 145 patients who had fullfilled the inclusion criteria.The data collected includes clinical patient characteristics, procedural measures, timestamp at each stage, and patient outcome. IV thrombolytics application, pre and post‐intervention imaging findings, device related adverse event and any type of intracranial hemorrhage were recorded. Results There was female pre‐dominance (54.5%). Median presenting NIHSS was 16 (IQR, 3–32). 88 MCA‐m1 (60,6%), 43 ICA‐tip (29,6%), 11 MCA‐m2 (7,5%), 2 ACA (1,4%) and 1 basilar (0,7%) occlusions were underwent for mechanical thrombectomy. Median procedure time was 25 min (IQR, 7–136). First‐pass reperfusion scores were mTICI 0–2a 22.7%, mTICI 2b 23.4%, mTICI 2c 17.9% andmTICI 3 35.9%.Mean number of pass was1,84±1,14.Final mTICI 2b‐3 score was 97.9% and TICI2c‐3 score was 87.6%. No device related adverse event occurred. The mean 24‐hour NIHS score was 6 (IQR 0–33). Conclusions In conclusion, the NeVa thrombectomy device offers a high rate of first‐pass success along with favorable safety profile. Larger series and multi‐center studies are needed for further investigation